2008
DOI: 10.1177/1050651907307710
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a Hybrid Format

Abstract: As college instructors endeavor to integrate technology into their classrooms, the crucial question is, “How does this integration affect learning?” This article reports an assessment of a series of online modules the author designed and piloted for a business communication course that she presented in a hybrid format (a combination of computer classroom sessions and independent online work). The modules allowed the author to use classroom time for observation of and individualized attention to the composing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A key element of reflective practice, of course, is assessment, and teachers have originated an assortment of frameworks for evaluating the integration of technology in technical communication instruction (cf. Jablonski & Nagelhout, 2010; Katz, 2008; Morain & Swarts, 2012). In one assessment effort, Manion and Selfe (2012) discovered a mismatch between their current grading routines and the affordances of wikis.…”
Section: Technology Integration and Use In The Classroommentioning
confidence: 99%
“…A key element of reflective practice, of course, is assessment, and teachers have originated an assortment of frameworks for evaluating the integration of technology in technical communication instruction (cf. Jablonski & Nagelhout, 2010; Katz, 2008; Morain & Swarts, 2012). In one assessment effort, Manion and Selfe (2012) discovered a mismatch between their current grading routines and the affordances of wikis.…”
Section: Technology Integration and Use In The Classroommentioning
confidence: 99%
“…Appropriately enough, much of the academic discussion regarding online education in criminal justice has focused on assessment and pedagogy (e.g., Johnson 2005;Katz 2008;Thomas 2000), curricular development (e.g., Snell and Penn 2005), and student satisfaction with distance learning (e.g., Maki, Maki, Patterson, and Whittaker 2000;Mayzer and DeJong 2003). There is limited literature available that provides an in-depth discussion on the impact of program development on faculty members.…”
Section: The Impact Of Online Teaching and Learning On Faculty Membersmentioning
confidence: 99%
“…The student survey results also showed high satisfaction and a high probability of enrolling in another hybrid course in the future. Katz (2012) is another researcher who used an indirect student survey measure along with a direct measure, which involved blind reviews of student work in assessing a hybrid business communication course. The survey results showed that students felt the course was effective in teaching important concepts.…”
mentioning
confidence: 99%